(untitled) (UNED Research Journal, 2021)
Introduction: Currently, many animals leave protected wild areas in search of resources, suffering conflicts with people from nearby areas. Objective: To evaluate the conflicts between people and fauna in the Buffer Zone of La Amistad International Park, Costa Rica. Methods: We applied semi-structured interviews and questionnaires in five communities. Results: The most conflictive species in agriculture were Ortalis cinereiceps, Atta cephalotes and Phyllophaga sp.; and in livestock, Panthera onca, Desmodus rotundus and Canis latrans. Losses amount to US44,000, with Tres Colinas and Santa María de Brunka being the most affected communities, although their inhabitants have both positive and negative opinions of these animals. Conclusion: Six species cause most of the losses in the area, but the inhabitants differ in their perception.